2005
DOI: 10.2741/1521
|View full text |Cite
|
Sign up to set email alerts
|

The immune system in aging: roles of cytokines, T cells and NK cells

Abstract: Aging is characterized by a proinflammatory state that contributes to the onset of disability and age-related diseases. Proinflammatory cytokines play a central role in mediating cellular and physiological responses. The levels of these cytokines may reflect immune system effectiveness. Studies of the effects of aging on inflammatory response show interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha) and interleukin-1beta (IL-1beta) to be important. In this review, age-related changes in inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 321 publications
(221 reference statements)
3
58
1
3
Order By: Relevance
“…There was a great individual variability in mRNA expression levels of the different cytokines in dogs with FRD, IBD and even in control dogs. Differences in age, growth, sex and (or) nutritional status probably also accounted for the variability in cytokine mRNA profiles, in agreement with studies in humans (Moxley et al, 2002;Grimble, 2003;Huang et al, 2005). However, there were significant gender influences on INF-γ mRNA levels of FRD dogs and on IL-13 mRNA levels in IBD dogs in duodenal samples.…”
Section: Discussionsupporting
confidence: 75%
“…There was a great individual variability in mRNA expression levels of the different cytokines in dogs with FRD, IBD and even in control dogs. Differences in age, growth, sex and (or) nutritional status probably also accounted for the variability in cytokine mRNA profiles, in agreement with studies in humans (Moxley et al, 2002;Grimble, 2003;Huang et al, 2005). However, there were significant gender influences on INF-γ mRNA levels of FRD dogs and on IL-13 mRNA levels in IBD dogs in duodenal samples.…”
Section: Discussionsupporting
confidence: 75%
“…Although the possibility does exist that women in our study with evidence of long-term HPV positivity have repeated viral acquisition over time rather than true viral persistence, our findings suggest that weaker cellular immune function may be strongly associated with length of HPV persistence. Stratification of our data by age indicated that the primary effect was evident among women 65 years of age and older, an age group where immune senescence has been previously reported (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Surprisingly, however, we did not observe evidence of age-related immune decline in our HPV-negative control group.…”
Section: Discussionmentioning
confidence: 95%
“…This second peak in HPV prevalence is poorly understood and could be due to cohort effects, re-exposure through new sexual contacts, and/or physiologic changes at the cervix with aging that increase the efficiency of HPV detectability by current sampling methods (25,26). It has also been suggested that this second peak might occur due to reemergence of latent HPV infections in older women (27), following age-related declines in immunologic competence (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the balance of the pro-inflammatory/anti-inflammatory pathways, lymphocytes activation and hepatocellular stimulation of acute phase protein synthesis [43]. Studies of the effects of ageing on inflammatory response show interleukin-6 (IL-6) to be an important ''cytokine for gerontologists'' [42,72]. Indeed, an age-related increase of IL-6 concentrations has been found in serum, plasma and supernatants of mononuclear blood cell cultures from elderly people devoid of any overt age-related diseases [44,45], beginning as early as 30-40 years of age [111] and being prominent among men [160] and in centenarians [8].…”
Section: Zinc-interleukin-6 Gene Interactionmentioning
confidence: 99%